RADIATION DOSE IS OF LIMITED CLINICAL USEFULNESS IN PERSONS WITH ACUTE RADIATION SYNDROME. Issue 1 (25th April 2019) - Port, Matthias; Majewski, Matthäus; Abend, Michael
Abstract: The relation of radiation exposure (dose) with acute radiation syndrome (ARS) depends on many factors. In this overview, we reconsider (1) radiation exposure characteristics (e.g. radiation quality, fractionation, dose rate, partial/total body irradiation) and (2) biological processes (e.g. radiosensitivity, cell cycle dependency, oxygenation) affecting acute health effects after exposure. Furthermore we include evidence from recently published work that examined the relationship of absorbed dose and risk of clinically relevant ARS in persons exposed after a radiation accident. We introduce the concept of radiation-related bioindicators for effect prediction. Bioindicators are considered here to be factors that integrate multiple radiation exposure characteristics and cell- and molecular-based processes to improve clinical prediction in persons with ARS.